Positive role of polyunsaturated fatty acids on sustainable crop production against salt stress: an overview - Srivastava, Smita; Yadav, Sagar (Biologia, 2024)
Abiotic stresses have become more severe and capricious due to global warming and varying climatic conditions, with increased temperature reducing the yield of important agricultural crops due to high evapotranspiration, resulting in the increased amount of soil salinization in arid and semi-arid areas, which has become a significant threat that restricts agricultural practices and leads to the overexploitation of cultivation land. One of the crucial environmental elements limiting plant development and yield is salinity. The special effects of salt stress on the superiority of numerous crops have yet to be discovered. Under salinity, plants tend to activate multiple physiological and biochemical mechanisms to overcome the stress by altering their morphology, photosynthesis, water relations, and biochemical adaptations, such as the antioxidative metabolism response and trigger polyunsaturated fatty acids (PUFAs), which act as a biomarker for salinity stress. With the help of PUFAs, which have become popular as all-purpose defenders, decorative techniques have been created to prevent the consequences of saline. The most prevalent PUFAs in plants are those with 18 carbons, specifically 18:1 (oleic), 18:2 (linoleic), and 18:3 (alpha-linolenic) acids which operate as glycerolipids, a source of energy and carbon in triacylglycerol, precursors of numerous bioactive chemicals, stores of extracellular barrier components, and intrinsic antioxidants, modulating cellular membranes and enhancing crop quality and yield. However, limited information about PUFAs and their roles in enhancing crop stress tolerance is available. Therefore, producers and breeders must understand salinity's influence on crop composition to enhance fatty acids under salinity conditions. However, brief work has been reported; this review will help comprehend the role of fatty acids in salinity for food security through the genetic engineering of synthetic genes encoding fatty acids to improve crop stress tolerance and grain quality.
Keywords: Cuticle wax; Membrane lipids; photosynthesis; Polyunsaturated fatty acid; ROS; salt stress; Sensing mechanism; stress tolerance